The psychological insight into low frustration tolerance in student’s age - Bozhok, Natalia (My University, 2012)
The sense and causes of appearance of low frustration tolerance in students’ age are discovered in the article. The syndrome of «low frustration tolerance» and factors contribution to decreasing its destructive effects are analyzed. The model of self-efficacy directed to the increasing of frustration tolerance is represented.
Keywords: низька фрустраційна толерантність; студентський вік; самоефективність; низкая фрустрационная толерантность; студенческий возраст; самоефективность; low frustration tolerance; student’s age; self-efficacy; кафедра ділової іноземної мови та міжнародної комунікації